Studying insects' response to short-term climate events. (Research'eu results magazine)
Studying the response of living organisms to climate change is essential in the face of what increasingly looks like an irreversible trend. However, unlike other species which have gathered much scientific attention, insects seem to have been left behind. An EU project is seeking to bridge this knowledge gap while taking insects' specific features into account.